2010
DOI: 10.1001/archoto.2010.154
|View full text |Cite
|
Sign up to set email alerts
|

Professional Burnout Among Microvascular and Reconstructive Free-Flap Head and Neck Surgeons in the United States

Abstract: Most MVFF surgeons experience moderate professional burnout secondary to moderate EE and DP. This may be a problem of proper balance between professional obligations and personal life goals. Most MVFF surgeons, nonetheless, experience a high level of personal accomplishment in their profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…Regarding working hours, both surgeons and residents work more than 40 hours/week, which is consistent with the findings of Porto et al, 12 who reported that majority of the OM surgeons worked 30–50 hours/week. Although Contag et al 28 reported that the number of working hours was not associated with the rate of burnout, in the present study, residents were more burned out due to long working hours ( P = 0.003). Furthermore, Hameed et al 29 conducted a similar study and explored the relationship between duty hours and burnout among medical residents in Saudi Arabia.…”
Section: Discussioncontrasting
confidence: 83%
“…Regarding working hours, both surgeons and residents work more than 40 hours/week, which is consistent with the findings of Porto et al, 12 who reported that majority of the OM surgeons worked 30–50 hours/week. Although Contag et al 28 reported that the number of working hours was not associated with the rate of burnout, in the present study, residents were more burned out due to long working hours ( P = 0.003). Furthermore, Hameed et al 29 conducted a similar study and explored the relationship between duty hours and burnout among medical residents in Saudi Arabia.…”
Section: Discussioncontrasting
confidence: 83%
“…The inability to accurately identify the receipt status of the electronic invitation to participate among members of the study population (see Methods) complicates the response rate calculation, and likely means that the response rate was higher than reported. Further, practice demographics from our sample compare favorably with those from a larger published study among microvascular and reconstructive free-flap head and neck surgeons, demonstrating very similar numbers of free-flap procedures performed annually, years in practice, and proportion in academic versus private practice [5]. However, these considerations do not eliminate the potential for non-response bias in our study.…”
Section: Discussionmentioning
confidence: 58%
“…Certain notable aspects of microvascular surgery in practice may contribute to physician burnout, as reported in a 2010 cross-sectional study of burnout among microvascular surgeons [5]. Respondents in that study, who were largely derived from academic practices, identified having too little time to do research, too little administrative time, and low levels of control over professional life as leading stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is likely great variability in personal and professional choices, factors such as aging/ fatigue, career stressors, burnout (emotional exhaustion/ diminished satisfaction), pursuit of research or other academic endeavors, and rapid evolution of the field may contribute to this phenomenon. [17][18][19][20] Our data show a clear trend toward implementation of the two-team approach within academic ORL-HNS programs, most commonly with H&N fellowship-trained otolaryngologists performing both ablative and reconstructive roles (95.1% of programs, weighted 75.1% of practice). The two-team approach to H&N reconstruction far predates the routine use of H&N MFTT.…”
Section: Discussionmentioning
confidence: 80%